Case Report: Malignant phyllodes tumor of the breast with heterologous osteosarcomatous differentiation and literature review - Guo, Liang; Wang, Jing; Li, Xiang; Dong, Xin; Lu, Xiaoqian; Cao, Dianbo (Frontiers in Oncology, 2025)
Phyllodes tumor (PT) of the breast is a rare fibroepithelial tumor characterized by the proliferation of both epithelial and stromal components. The presence of osteosarcomatous differentiation within the sarcomatous stroma is exceptionally uncommon and typically portends a poor prognosis. However, the biological behavior of malignant phyllodes tumors (MPT) exhibiting heterologous osteosarcomatous differentiation requires further investigation. A 59-year-old woman presented with a one-month history of a left breast lump. Mammography, chest CT, ultrasonography and MRI identified a mass measuring 3.7cm×5.6cm×4.7cm. Notably, the time-intensity curve derived from DCE-MRI demonstrated a pattern of rapid initial enhancement followed by slow washout. The patient underwent wide local excision, and postoperative histopathology examination confirmed MPT with heterologous osteosarcomatous differentiation, predominantly composed of neoplastic bone. The patient declined adjuvant therapy and was managed with regular follow-up. Twelve months later, she returned with a recurrent breast mass. Mammography and chest CT showed a calcified mass measuring 6.3cm×6.5cm, resembling the previous lesion. A total mastectomy accompanied by partial resection of the pectoral major muscle was performed. The histopathological examination of the second specimen was consistent with the initial diagnosis. Following the second surgery, the patient received four cycles of chemotherapy and was maintained on regular surveillance. Ten months later, follow-up CT imaging revealed extensive pleural effusion with complete passive atelectasis of the left lung, along with scattered patchy and curvilinear calcifications along the mediastinal and parietal pleura. The patient declined further chemotherapy and opted for traditional Chinese medicine, and she died three months later. MPT of the breast with heterologous osteosarcomatous differentiation is an exceedingly rare entity with a poor prognosis despite aggressive therapeutic interventions. Different from previously reported cases, our case elucidates the tumor’s biological behavior through serial image follow-up, and highlights its hypervascularity which was not detected by color Doppler ultrasound but was clearly demonstrated on DCE-MRI.